2016
DOI: 10.15252/embj.201593084
|View full text |Cite
|
Sign up to set email alerts
|

Mfn2 deficiency links age‐related sarcopenia and impaired autophagy to activation of an adaptive mitophagy pathway

Abstract: Mitochondrial dysfunction and accumulation of damaged mitochondria are considered major contributors to aging. However, the molecular mechanisms responsible for these mitochondrial alterations remain unknown. Here, we demonstrate that mitofusin 2 (Mfn2) plays a key role in the control of muscle mitochondrial damage. We show that aging is characterized by a progressive reduction in Mfn2 in mouse skeletal muscle and that skeletal muscle Mfn2 ablation in mice generates a gene signature linked to aging. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
283
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(309 citation statements)
references
References 65 publications
24
283
2
Order By: Relevance
“…Our findings here not only provide mechanistic correlation of SIRT1‐MFN2 axis in autophagy regulation in the liver but also explain why aged livers are intrinsically vulnerable to ischemic stress. While the involvement of SIRT1 in tissue aging has been well documented in various tissues, Zorzano's group recently reported that defective mitophagy and mitochondrial malfunction in skeletal muscles is causatively linked to a progressive loss of MFN2 with aging (Sebastián et al., 2016), substantiating an integral role of MFN2 in aging and mitophagy. Unlike the muscle, the expression of basal MFN2 or SIRT1 in old hepatocytes was comparable to that in young counterparts.…”
Section: Discussionmentioning
confidence: 74%
“…Our findings here not only provide mechanistic correlation of SIRT1‐MFN2 axis in autophagy regulation in the liver but also explain why aged livers are intrinsically vulnerable to ischemic stress. While the involvement of SIRT1 in tissue aging has been well documented in various tissues, Zorzano's group recently reported that defective mitophagy and mitochondrial malfunction in skeletal muscles is causatively linked to a progressive loss of MFN2 with aging (Sebastián et al., 2016), substantiating an integral role of MFN2 in aging and mitophagy. Unlike the muscle, the expression of basal MFN2 or SIRT1 in old hepatocytes was comparable to that in young counterparts.…”
Section: Discussionmentioning
confidence: 74%
“…However, how these functions are affected by deregulation of mitochondrial dynamics during aging, and whether alternate pro-longevity interventions require different mitochondrial network states and outputs remains unclear. Age-onset appearance of swollen, fragmented mitochondria has been reported across species (Jiang et al, 2015; Leduc-Gaudet et al, 2015; Sebastián et al, 2016), suggesting mitochondrial fragmentation (driven by fission) is pro-aging. Supporting this hypothesis, studies in yeast show inhibition of fission increases longevity, while unopposed fission shortens lifespan (Scheckhuber et al, 2007, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Dysregulation of mitochondrial dynamics and aberrant mitochondrial morphology are hallmarks of aging and are thought to contribute to the pathology of numerous age-related pathologies including Alzheimer’s and Parkinson’s disease (Bonda et al, 2011; Leduc-Gaudet et al, 2015; Sebastián et al, 2016). Mitochondrial dynamics regulate several key cellular functions, including metabolic plasticity, mitochondrial turnover, and inter-organelle communication (Wai and Langer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, HIF1a activation has been found in aged tissues, such as skeletal muscle, in old mice (22-30 months) 11,40 but not in middle-aged mice. 10 Sebastian et al demonstrated that gain of HIF1a activity in old or very old skeletal muscle leads to global mitochondrial dysfunction or mitochondrial autophagy, providing a molecular basis of skeletal muscle mitochondrial decline during aging.…”
Section: Age-dependent White Adipocyte Hif1a Expressionmentioning
confidence: 95%
“…10 Sebastian et al demonstrated that gain of HIF1a activity in old or very old skeletal muscle leads to global mitochondrial dysfunction or mitochondrial autophagy, providing a molecular basis of skeletal muscle mitochondrial decline during aging. 40 In skeletal muscle, Gomes et al also showed that gain of HIF1a expression has been Figure 2. Activation of HIF1a in aging white adipocytes.…”
Section: Age-dependent White Adipocyte Hif1a Expressionmentioning
confidence: 99%